Multimedia-based group guidance in assisting children reaching puberty in Central Lombok - Aulia, Fitri; Musifuddin, Musifuddin; Aisyah, Umi; Marfuatun, Marfuatun; Partha, I Dewa Putu (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aims to determine the effect of group guidance in assisting children reaching puberty in Central Lombok. The strategy uses group guidance and the media uses youtube videos and hands-on practice with tutorials. Group guidance services function as an understanding and prevention of deviant behavior during the transition from childhood to early adulthood. The research method used is experimental with pretest and posttest designs. Subjects consisted of 6 students aged 9-13 years. The topics discussed are 1) what and how puberty is, (2) the influence of puberty in the social environment, 3) the meaning of menstruation, and how to live a healthy lifestyle. Based on the data, the results of the pretest showed an average value of 21% and a standard deviation of 2.44%. The posttest results showed an average value of 24.8%, standard deviation of 4.49%. It shows that the enactment of group guidance is effective in increasing the understanding of puberty teenagers. Based on the satisfaction questionnaire after being given group guidance, a score of 20-24 is included in the very good category.